SISTEM PENGOLAHAN DATA ABSENSI KARYAWAN STMIK KHARISMA MAKASSAR - Devan Fryanto Buntu Pasau; Hamdan Arfandy; Abdul Munir (STMIK KHARISMA Makassar, 2019)
The purpose of this research is to design a website that can retrieve attendance data from the fingerprnit machine and then save it to the database and then display it to the website. The problem that arises is, to retrieve data from a fingerprint machine, the computer is first installed an application provided by the fingerprint machine provider company to be able to retrieve data from the fingerprint machine. The author makes a website so that the process of retrieving data from the fingerprint machine can be done by accessing the website. Websites created by authors can only be accessed in the same network. The author describes the system processes that are running by using a use case diagram. Authors use activity diagrams to describe system workflows in applications. To describe the structure of a web application, the author uses the Entity Relationship Diagram. The author uses the blackbox method for testing applications. The results of this study the author managed to design and create a website that can retrieve data from the fingerprint machine.